Lider czy liderka? Konsekwencje stosowania feminatywów dla postrzegania przywództwa - Anna O. Kuźmińska (Studia i Materiały)
According to the Implicit Leadership Theory, leadership roles are assigned in the process of social construction and depend upon the level of congruence with the cognitive representation of a leader. Previous studies show that this cognitive representation is much more likely to involve a leader being a male rather than a female. The article presents the results of an experiment aimed at tentatively verifying whether the use of the feminine forms could increase the cognitive availability of the representation of a woman as a leader. In the experiment, 135 teams (N = 307 respondents) were randomly assigned to one of two experimental conditions: 1) generic instruction (without the use of feminatives, “Please, draw a leader”), 2) inclusive instruction (using feminatives, “Please, draw a leader/leaderess”). The results showed a significant interaction between the experimental manipulation and the proportion of women in the team. The use of feminine forms increased the percentage of females drawn as leaders only in teams with a high female-to-male ratio.